Statistical physics - Sator, Nicolas; Couëdel, Lénaïc; Pavloff, Nicolas (Boca Raton, FL CRC Press, an imprint of Taylor and Francis Group, LLC, 2024)
"This book presents an introduction to the main concepts of statistical physics, followed by applications to specific problems and more advanced concepts, selected for their pedagogical or practical interest. Particular attention has been devoted to the presentation of the fundamental aspects, including the foundations of statistical physics, as well as to the discussion of important physical examples. Comparison of theoretical results with the relevant experimental data (with illustrative curves) is present through the entire textbook. This aspect is facilitated by the broad range of phenomena pertaining to statistical physics, providing example issues from domains as varied as the physics of classical and quantum liquids, condensed matter, liquid crystals, magnetic systems, astrophysics, atomic and molecular physics, superconductivity and many more. This textbook is intended for graduate students (MSc and PhD) and for those teaching introductory or advanced courses on statistical physics"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Statistical physics -- Textbooks